Iodine(III)-Mediate Oxidative Cyanation, Azidation, Nitration, Sulfenylation and Slenization in Olefins and Aromatic Systems - Segura-Quezada, Luis A.; Torres-Carbajal, Karina R.; Juárez-Ornelas, Kevin A.; Navarro-Santos, Pedro; Granados-López, Angélica J.; González-Garci#129;a, Gerardo; Ortiz-Alvarado, Rafael; de León-Solis, Claudia; Solorio-Alvarado, César R. (Current Organic Chemistry, 2022)
Iodine(III) reagents represent nowadays a class of highly relevant oxidants in organic synthesis which possess important properties such as safer, non-toxic, green and easy to handle compounds. These characteristics, in several cases, make them important alternatives to the procedures which use hazardous and strong reaction conditions. Based upon their ability as oxidants, they have been exploited in the functionalization of the different aromatic nuclei, allowing the introduction of several groups: among them, inorganic functionalities. Herein, the most relevant developed protocols for functionalizing a broad amount of aryls, heteroaryls and olefins are summarized by introducing the inorganic groups cyano, azido, nitro, sulfur and selenium, using different iodine(III) reagents.
Keywords: nitration